2008
DOI: 10.1016/j.jcrysgro.2008.08.041
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of InAs quantum dots optical properties in close proximity to GaAs(001) substrate surface

Abstract: In this work we demonstrate a growth process for obtaining high optical emission efficiency InAs/GaAs(001) quantum dots (QD) formed at short distance to the interface with the GaAs substrate. In particular, after an initial exposure of the substrate surface to long times of atomic hydrogen flux (t H up to 45 min) followed by a posterior growth of a GaAs buffer layer by atomic layer molecular beam epitaxy, both steps at low substrate temperature (T S =450 ºC), an enhancement of InAs QD optical emission efficien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 25 publications
(32 reference statements)
1
13
0
Order By: Relevance
“…The line-widths found here are of the same order as those reported for InAs SCQDs grown near to re-growth interface on nanohole patterned substrates fabricated by different lithographic techniques [11,12,45]. Higher annealing temperature or longer atomic hydrogen treatments of the re-growth interface than used in this work [23] will be crucial to further reduce spectral diffusion effects and to improve the optical quality. In this sense, Jöns et al have demonstrated the growth of InAs SCQDs with a median optical line-width value of 13μeV in e-beam lithography patterned substrates located only at 22nm from the re-growth interface that match the optical properties of self-assembled InAs QD [32].…”
Section: Resultssupporting
confidence: 77%
See 1 more Smart Citation
“…The line-widths found here are of the same order as those reported for InAs SCQDs grown near to re-growth interface on nanohole patterned substrates fabricated by different lithographic techniques [11,12,45]. Higher annealing temperature or longer atomic hydrogen treatments of the re-growth interface than used in this work [23] will be crucial to further reduce spectral diffusion effects and to improve the optical quality. In this sense, Jöns et al have demonstrated the growth of InAs SCQDs with a median optical line-width value of 13μeV in e-beam lithography patterned substrates located only at 22nm from the re-growth interface that match the optical properties of self-assembled InAs QD [32].…”
Section: Resultssupporting
confidence: 77%
“…Conventional thermal oxide desorption at high temperature is not compatible with the growth on patterned substrates due to surface pitting [21]. Instead, other techniques, such as atomic H treatment [22,23], Ga assisted oxide desorption [24] or special chemical native oxide removal processes [25], are suitable for patterned substrates. Furthermore, growth of thick buffer layers or growth at high temperature should be avoided due to the smoothening of the patterned motifs, in order to preserve the selectivity and control of the QD formation in the nanoholes.…”
Section: Some Common Epitaxial Procedures Might Have An Undesired Impmentioning
confidence: 99%
“…Many works have been performed over several decades in order to get a proper passivation of III-V compound semiconductor surfaces mostly for electronics devices [22][23][24][25][26][27][28]. Such methods have been recently employed also for improving the performance of optical devices [11,22,[29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…19,20 This process efficiently removes the surface oxide and provides a clean surface suitable for epitaxial regrowth. 21 Atomic H treatment is monitored by reflection high energy electron diffraction (RHEED). Specular spot shows up in less than 2 min after the H treatment starts and a 2× RHEED pattern along [11̅ 0] direction is observed during this cleaning treatment.…”
Section: Methodsmentioning
confidence: 99%